Penerapan Metode Failure Mode Effect And Analisys (FMEA) Pada Proses Penambahan Gudang - Della Afi Rizky Anggraini; Minto Waluyo (Pusat Riset dan Inovasi Nasional, 2024)
This research uses the Failure Mode Effect and Analysis (FMEA) method which is used to evaluate and analyze the causes of problems in the process of adding a new warehouse due to overstorage in the fertilizer storage warehouse. Where in this research it is known that the dominant causal factor that causes this problem is that it is difficult to obtain a warehouse according to the location needed and the warehouse procurement process takes quite a long time. From these dominant problems, alternative improvements were obtained to overcome these problems so that the process of adding a new warehouse could run effectively and efficiently in terms of time and cost